Sleepyhead [compact disc, unabridged] - Billingham, Mark (Billingham, Mark. DI Tom Thorne series., 2013)
Alison Willetts is unlucky to be alive. She has survived a deliberately induced stroke, and although she can see, hear, and feel, she is completely unable to move or to communicate. In leaving Alison alive, the police believe her assailant has made his first mistake. Until Detective Inspector Tom Thorne discovers the horrifying truth: Alison is the psychopath's first success; the three women he killed before her were the mistakes.